EGO DEFENSE MECHANISM OF THE MAIN CHARACTER IN NEIL GAIMANS THE OCEAN AT THE END OF THE LANE - Azahra, Malva Adinia; Setyowati, Agnes; Widisanti, Ni Made (Journal Albion : Journal of English Literature, Language, and Culture, 2022)
This study analyzes the main characters defense mechanisms when experiencing conflict in Neil Gaimans The Ocean at the End of the Lane. This research uses descriptive analysis method with a literary psychology approach that focuses on Sigmund Freuds psychoanalytic theory regarding defense mechanism. The research technique is library research. The research findings reveal that the main character performs defense mechanisms such as rationalization, sublimation, denial, identification, and repression when he encounters unwanted feelings.Keywords: main character; defense mechanism; psychoanalysis; literary psychology; anxiety.